Ending the food fight : guide your child to a healthy weight in a fast food/fake food world - Ludwig, David , 1957-; Rostler, Suzanne (Houghton Mifflin, 2007)
Harvard endocrinologist Ludwig pioneered the use of a low-glycemic diet in combating obesity. Ten years ago, Dr. Ludwig founded the Optimal Weight for Life Program (OWL) at Children's Hospital Boston. There he and his team tailored his low-glycemic diet for children and combined it with a nine-week progressive plan that benefits the patient and the entire family. This scientifically proven approach addresses, for the first time, all three key factors affecting body weight--biology, behavior, and environment--and integrates them into a practical prescription for weight loss. It also recognizes the challenges children and their parents face in today?s toxic food world. We are surrounded not only by high-calorie, low-quality fast food, but also by more and more "fake food": processed foods unlike anything found in nature. Here, Dr. Ludwig shares his program with parents, giving them the tools they need to help their children win the food fight.--From publisher description